Sappho : the only lesbian magazine in Europe ; vanaf 07(1979-1980) 2 : lesbian feminist voice. (London : Sappho Publications, 1973)
Fonds Suzan Daniel (FSD)
Periodiciteit : maandelijksRedactie : BCM/Pterel, London WC1V 6XX ; vanaf 04(1975-1976) 2 : 39 Wardour Street, London W1V 3HA ; vanaf 04(1975-1976) 12 : 20 Dorset Square, London NW1 6QB
Engels
Periodiek